AML/CFT Regulation : Implications for Financial Service Providers that Serve Low-Income People - Hernandez-Coss, Raul (World Bank, Washington, DC, 2021)
Across the world, new measures are being introduced and existing measures tightened to combat money laundering and the financing of terrorism. All financial service providers, including those working with low-income communities, are-or will-be affected by these measures. This paper summarizes the implications of the international framework for anti-money laundering (AML) and combating the financing of terrorism (CFT) for financial service providers working with low-income people. The international AML/CFT standards developed by the Financial Action Task Force (FATF), generally requires financial service providers to enhance their internal controls to cater specifically for AML/CFT risks; undertake customer due diligence procedures on all new and existing clients; introduce heightened surveillance of suspicious transactions and keep transaction records for future verification; and report suspicious transactions to national authorities. These measures could bring additional costs of compliance to financial service providers; and customer due diligence rules may restrict formal financial services from reaching lower-income people. The introduction of new or tightened AML/CFT regulations may have the unintended and undesirable consequence of reducing the access of low-income people to formal financial services. As a means to avoid this outcome, this paper argues in favor of (1) gradual implementation of new measures; (2) the adoption of a risk-based approach to regulation; and (3) the use of exemptions for low-risk categories of transactions.